Film style and technology : history and analysis - Salt, Barry (London : Starword, 2009)
This book contains : * The first and only full histoy of film style ; * The only valid analysis of the relation of film style to film technology * New methods for the formal analysis of films and a demonstration of their use ; * A new practical approach to film theory ; * The application of all of the above to an analysis and evaluation of the films of Max Ophuls ; * The first completely reasoned demolition of recent film theorizing : * 183 half-tone illustrations, and many line diagrams, tables, and histograms
Str. [401]- 403: Bibliografija
Rječnik i kazalo.
Keywords: film; filmska tehnologija -- filmski stil; filmski stil -- povijest; povijest filmskog stila